Agricultural Innovation and Sustainable Food Security: Evidence from the South-South Geographical Zone of Nigeria - Joel Dimiyen Bisina; Ugo Chuks Okolie (Pinisi Journal of Social Science, 2025)
Innovation in agriculture and the pursuit of sustainable food security are vital concerns for all modern societies. In this context, the present study conducted an empirical investigation to assess the relationship between agricultural innovation and sustainable food security in Nigeria’s South–South geopolitical zone. A cross-sectional research design was adopted, and data were gathered through a survey administered to 300 respondents across the region. The data were analysed using linear regression and the Pearson product–moment correlation, with the assistance of the Statistical Package for the Social Sciences (SPSS) version 23. The findings revealed a strong and positive association between agricultural innovation and sustainable food security in the South–South zone. As anticipated, the study further showed that agricultural innovation exerts a favourable and statistically significant influence on sustainable food security in the area. It also explored the implications of food security for Nigeria’s national security. Overall, the results suggest that agricultural innovation plays a crucial role in achieving sustainable food security globally. Consequently, the study recommends, among other measures, that both federal and state governments in Nigeria should strengthen agricultural research and capacity building through the use of modern technologies, with a view to boosting agricultural productivity and enhancing food security nationwide.